Pengaruh Strategi Promosi Terhadap Perkembangan Jumlah Debitur Pada PT. Adira Finance Di Tenggarong - Erwinsyah, Erwinsyah (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2015)
The purpose of this study is to know and examine the magnitude of promotional effects consisting of advertensi, sales promotion, personal selling and publicity to the development of the number of debtors in PT. Adira Finance Tenggarong Branch. In an effort to maintain the viability of its business, the PT. Adira Finance Tenggarong Branch has the purpose of always trying to attract as many debtors as possible, because the debtor is the main source of income of PT. Adira Finance. But the fact that promotion that has been done as expected because the number of new debtors that can be obtained by PT. Adira Finance is far from the desired target. Achievement of the number of debtors who are still far from the target certainly could have a negative impact for the survival of the business of PT. Adira Finance in the future. This research is done by using quantitative method. Data collection techniques with observation, questionnaires and library research. The process of data analysis and calculation using multiple regression analysis. Hypothesis testing using F test and t test. The multiple regression equation as follows Y = - 322.222 + 5.248.X1 + 6.301.X2 + 6,611.X3 + 5,750.X4. The result of the multiple regression equation can be known (a) of 322,221 that if advertence, personal selling, sales promotion and publication variables are absent, the amount of debtors will always remain constant decreased by 322,221. Result of calculation of test of F (simultaneous correlation ), obtained F count is 29,206, while value of F table obtained value equal to 3,11 this mean that (F valued 29,206> F table 3,11), so it can be said advertensi variable, personal selling, sales promotion and publication and simultaneously able to show the influence on the development of the number of debtors or can be said that the regression model built can be used to predict the development of the number of debtors in PT.Adira Finance Tenggarong Branch. Then the first hypothesis is accepted. Of the four partial correlation test results above shows the largest value of personal selling variables compared to other variables that amounted to 0.635 then followed by publicity 0.507, advertence variables of 0.484 and sales promotion variable of 0.190. From the description, it can be concluded that the second hypothesis in this study was rejected. Keyword: Debtors, Promotion